INFORMATION COMPETENCE OF FUTURE DOCTORS OF PHILOSOPHY AS AN INTEGRATIVE INDICATOR OF EFFECTIVE RESEARCH ACTIVITY - Iryna V.Oliinyk (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
In the article the definitional analysis of the concept of «information competence» is performed and the author’s own definition of this term is formulated. Based on the theoretical analysis of the study of this problem, the main components of the concept are determined from the point of view of information competence as a component of research. The main components of the general competence of a teacher-researcher, as well as the interdependence of professionalism, information and research competence are determined. The most effective technologies for the formation of information competence in future Ph.Ds. are justified. The relevance of the acquisition of future Ph.D’s. information competence in the conditions of research activity has been proved. The main skills of a future Ph.D. in the context of information competence were revealed, determining their readiness to work in the new conditions of informatization of education. Based on the synthesis of the analyzed scientific views on the structure of information competence and taking into account the research aspect, the structural analysis of information competence was implemented.